WORKING PARAMETERS EFFECTS OF AIR CAPACITY REGULATION SYSTEM FOR RECIPROCATING COMPRESSOR UNDER DIFFERENT LOAD CONDITIONS - WANG Meng; WANG Yao; ZHANG JinJie (Jixie qiangdu)
Due to the fluctuations for high-pressure gas, the displacement of reciprocating air compressor needs to follow the change in requirements. At present, the regulating methods can be applied, including the refluxing regulation, the variable speed adjustment and the pressing-off inlet valve regulation. Among them the pressing-off inlet valve regulation has the best effect, but its control technique and structural modification are relatively difficult. In this paper, according to the demand of the air capacity regulation for reciprocating compressor, an improved operating cycle model of air compressor under the capacity regulation was established. The behaviors of the netted valves and the changes of the pressure in cylinder were analyzed. Additionally, different control parameters in the air capacity regulation system were numerically simulated, the different regulating effects are obtained. The influence of the above parameters was analyzed, which lays the foundation for the system optimization design.